ESP PRACTITIONERS’ ROLES AT VOCATIONAL SCHOOL - Mayuasti, Mayuasti (Universitas PGRI Sumatera Barat, 2019)
Having a profession as a Vocational English teacher means having to be prepared to carry out 5 important roles. Research shows that vocational English teachers today have not carried out all of these roles. With a qualitative approach, vocational English teachers are chosen as participants. Using observational and interview records, this research data is collected. The results illustrate that vocational English teachers have carried out all the roles in question, namely as teachers, as material providers and learning designers, researchers, collaborators and evaluators. However, the level of achievement of each role varies. It can be concluded that vocational English teachers have not maximized their role as ESP practitioners who are tasked with determining, designing, observing, and evaluating English learning.